Smart polymers: Challenges and future - Hernandez-Martinez AR (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2022)
According to the International Union of Pure and Applied Chemistry (IUPAC) Smart Polymers (SP) or stimulus-responsive polymers are "polymers that respond or that is designed to respond to a stimulus like pH, light, heat, etc. change, and provides a predetermined action". These changes are generally abrupt and relatively large, involving changes in phase or properties due to structural adaptations of the polymer [1-4].